Terrestrial Paradise in the Greek Life of Adam and Eve - Levison, John R. (Jack) (2018)
The Greek Life of Adam and Eve is dense with more than three dozen references to ??????????, yet paradise in the Greek Life has received scant attention. This article, which comprises the first sustained study of paradise in the Greek Life of Adam and Eve, brings to light a distinctive ancient portrait of terrestrial paradise encircled by a wall with openings and a door, flourishing with deciduous trees and fragrant plants, centered around two trees-but not the trees of Eden-and skirted by regions along its outer edge. In short, paradise, conceived in the Greek Life of Adam and Eve primarily as a terrestrial ??????????, is not the heavenly paradise that much of modern scholarship would have it be.
Keywords: Adam and Eve; Eden; Eschatology; Gardens; Heaven; Holiness; Paradise; Temple